IMPLEMENTASI METODE STEINBERG UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA KELAS RENDAH T.A 2021/2022 - Rini Ramadhani (PROCEEDING UMSURABAYA, 2022)
This study aims to determine the development of the application of the Steinberg method in learning Indonesian to improve students' creative thinking. The research subjects were grade 1 students at SDN Kuala Baru Laut, Aceh Province. This type of qualitative research with a case study design in the field. The method used in this research is the Steinberg method powerpoint based. The results of the analysis were then compared with the criteria for creative thinking to determine the level of application of the method in learning Indonesian. The application of the Steinberg method in class 1 Kuala Baru Laut achieved a score of 86%.Â Keywords: Steinberg method; Creative thinking; Indonesian; elementary school students.